Navigating the waves: understanding the long-term impact of COVID-19 on cruise industry employees' job satisfaction, turnover intentions, and word-of-mouth - Hoh, Kah Yee (Nanyang Technological University, 2023)
Purpose – Once on a trajectory of remarkable growth, the cruise industry faced an unprecedented crisis with the outbreak of COVID-19. This research's primary purpose was to look into the aftermath of this crisis, focusing on the workforce of the cruise industry and their intentions to remain in the field. As cruise lines grappled with labor shortages and operational challenges, this study sheds light on the pandemic’s long-term effects on employees' job security, mental well-being, and commitment to the industry by employing a comprehensive framework integrating event system theory and occupational stress models. Design/ Methodology/ Approach – A survey was conducted to test the COVID-19 impact on cruise industry employee perception on six construct items, namely COVID-19 event strength (CES), job insecurity (JI), mental health (MH), job satisfaction (JS), negative word-of-mouth (NWOM), and turnover intention (TI). A total of 81 responses were included and analyzed. The results first went through reliability analysis to assess the validity and consistency of all measurement items, resulting in the removal of JI and MH. Factor analysis was applied to identify three constructs of job satisfaction – contentment, work environment, and empowerment developing a new construct model. Factors were examined via a two-tail independent sample T-test to determine whether there was a significant difference between groups of gender. ANOVA tests were conducted to find out if there were significant differences in respondent groups according to age, education level, employment tenure, and length of stay in the industry. Lastly, multiple regression analyses were used to test the relationship between COVID-19 event strength, contentment, work environment, empowerment, negative word-of-mouth, and turnover intention. Findings – The research revealed an alarming impact on employees' perceptions of job security and mental well-being. Results indicated a significant link between COVID-19 stressors, job satisfaction, and employees' intentions to leave the industry. Insights derived from the study carry vital implications for industry practitioners, highlighting the importance of addressing job empowerment, employee contentment, and effective communication strategies to navigate the challenges posed by the lingering effects of the pandemic. Keywords: Coronavirus disease 2019 (COVID-19); Cruise industry; Job insecurity; Well-being; Turnover intention; Job satisfaction; Negative word-of-mouth